2016
DOI: 10.4174/astr.2016.91.4.178
|View full text |Cite
|
Sign up to set email alerts
|

Long-term oncologic outcomes of neoadjuvant concurrent chemoradiotherapy with capecitabine and radical surgery in locally advanced rectal cancer: 10-year experiences at a single institution

Abstract: PurposeOral capecitabine has demonstrated to be safe and efficient as neoadjuvant concurrent chemoradiotherapy (NCRT) for locally advanced rectal cancers. The aim of this study was to evaluate the long-term oncologic outcomes of NCRT with capecitabine and radical surgery.MethodsFrom January 2000 to June 2010, 238 patients were treated at our center for locally advanced rectal cancers using conventional NCRT with capecitabine and radical surgery. Univariate and multivariate analyses were used to evaluate the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recent studies showed that, despite nCRT with TME improving oncologic outcomes, patients with rectal cancer who have mLPLN have poor outcomes [ 21 22 ], and patients with locally advanced rectal cancer have a 10%–25% chance of developing mLPLN [ 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that, despite nCRT with TME improving oncologic outcomes, patients with rectal cancer who have mLPLN have poor outcomes [ 21 22 ], and patients with locally advanced rectal cancer have a 10%–25% chance of developing mLPLN [ 23 24 ].…”
Section: Discussionmentioning
confidence: 99%